PELATIHAN OPTIMALISASI PENGOLAHAN DATA KESEHATAN DI PUSKESMAS KANDA - Rasna, Rasna; Nurhayati, Siti; Sah, Andrian; Tonggiroh, Mursalim; Widiyantoro, Riandi; Prasetianingrum, Septyana (Gapenas Publisher, 2025)
Primary health care in Indonesia, especially in regions like Papua, faces major challenges in managing accurate, complete, and timely health data. At Puskesmas Kanda, data management is still done manually or semi-digitally using basic Microsoft Excel, which causes the recording and reporting process to be slow and error-prone. This condition has a negative impact on the quality of reports and data-based decision making by the management of the Puskesmas and the Health Office, contrary to the mandate of Permenkes No. 31 of 2019 concerning Health Information Systems. The purpose of this Community Service (PkM) activity is to increase the capacity of health workers at the Kanda Health Center in optimizing the use of Microsoft Excel for health data processing. The training provided included data validation techniques, the use of logical and statistical functions, the creation of visual graphs and dashboards, and the development of data recap templates that fit the real needs in the field. The results of the training showed significant improvement in participants' ability to manage and analyze health data efficiently. The evaluation showed a very high level of participant satisfaction with the benefits of the training (90%), the quality of the materials (89%), and the relevance to daily work needs (92%). With participatory learning methods and hands-on practice, the training successfully supported the digital transformation of health services.